2010
DOI: 10.2337/db10-0450
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Chimerism Permits Low-Dose Islet Grafts in the Liver or Pancreas to Reverse Refractory Autoimmune Diabetes

Abstract: OBJECTIVETo test whether induction of chimerism lowers the amount of donor islets required for reversal of diabetes and renders the pancreas a suitable site for islet grafts in autoimmune diabetic mice.RESEARCH DESIGN AND METHODSThe required donor islet dose for reversal of diabetes in late-stage diabetic NOD mice after transplantation into the liver or pancreas was compared under immunosuppression or after induction of chimerism. Recipient mice were monitored for blood glucose levels and measured for insulin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 48 publications
(69 reference statements)
0
28
1
Order By: Relevance
“…Although induction of chimerism alone was not able to reverse late-stage T1D that has little or no residual islet b-cells, combination therapy with administration of growth factors was able to augment b-cell neogenesis and cure a majority of late-stage T1D (23). In addition, induction of chimerism allowed a small numbers of donor islets (1 of 20 of regular dose) to reverse late-stage T1D after implanting islet grafts in the liver or native pancreas (26). Therefore, induction of mixed chimerism is an important curative therapy for late-stage T1D.…”
Section: Immunology and Transplantationmentioning
confidence: 99%
See 3 more Smart Citations
“…Although induction of chimerism alone was not able to reverse late-stage T1D that has little or no residual islet b-cells, combination therapy with administration of growth factors was able to augment b-cell neogenesis and cure a majority of late-stage T1D (23). In addition, induction of chimerism allowed a small numbers of donor islets (1 of 20 of regular dose) to reverse late-stage T1D after implanting islet grafts in the liver or native pancreas (26). Therefore, induction of mixed chimerism is an important curative therapy for late-stage T1D.…”
Section: Immunology and Transplantationmentioning
confidence: 99%
“…Antibodies for CD24(30-F1), CD4(GK1.5), IgM(II/41) IgD (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), BP1(6C3), CD19(eBio1D3), CD43(eBioR2/60), and CD23(B3B4) as well as efluor 450-labeled streptavidin were purchased from eBioscience (San Diego, CA). Dead cells were excluded using DAPI or aqua fluorescent reactive dye (Invitrogen, Carlsbad, CA).…”
Section: Flow Cytometry and Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, induction of MHC-mismatched mixed chimerism is able to reverse autoimmunity in mouse models (10,11). In particular, we have reported that induction of mixed chimerism under a radiation-free anti-CD3/CD8 conditioning regimen reversed autoimmune type 1 diabetes (T1D) and systemic lupus (12)(13)(14)(15)(16)(17)(18)(19). Induction of MHC-mismatched mixed chimerism can restore central tolerance by deleting autoreactive thymocytes with cross-reactivity (18), and tolerize residual T cells in the periphery and delete preexisting and immature autoreactive B cells (15,17).…”
mentioning
confidence: 99%